Cooperacion internacional - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
Activities of international cooperation during 1981 are listed. Training courses in cassava production, tissue culture, physiology, and in advanced research for postgraduate work were attended by 38 professionals from 16 countries. From 1973 to 1981 cassava hybrid seeds have been distributed in Latin America, North America and Europe, Asia, Africa, and other regions. Cassava program scientists visited the national programs of several Latin American and Asian countries to follow up the progress in cassava research and gather information. The most important trials carried out and results obtained in the countries visited are indicated. CIAT germplasm selections and hybrid materials provide opportunities for var. selection in national programs; germplasm exchange needs more training efforts in cassava tissue culture to reduce the risk of disease transmission. It is considered that the impact of research has thus far not reached the farmers due to the long time required to test and then multiply new cassava genotypes and that crop expansion for industrial purposes must be integrated with drying, processing, utilization, and commercialization. (CIAT)